2021
DOI: 10.3390/antibiotics10091079
|View full text |Cite
|
Sign up to set email alerts
|

Mucormycosis in Indian COVID-19 Patients: Insight into Its Patho-Genesis, Clinical Manifestation, and Management Strategies

Abstract: Mucormycosis in patients who have COVID-19 or who are otherwise immunocompromised has become a global problem, causing significant morbidity and mortality. Infection is debilitating and fatal, leading to loss of organs and emotional trauma. Radiographic manifestations are not specific, but diagnosis can be made through microscopic examination of materials collected from necrotic lesions. Treatment requires multidisciplinary expertise, as the fungus enters through the eyes and nose and may even reach the brain.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 137 publications
(160 reference statements)
0
17
1
3
Order By: Relevance
“…In mucormycosis, patients, an early sign of the disease is facial cellulitis, paresthesia, nasal discharge, necrotic turbinate, fever, headache, and lethargy. [ 7 ] However, many of these symptoms were absent in this patient, in contrast to other findings. Squamous cell carcinoma of the maxillary sinus or malignant salivary gland tumor arising from the accessory glands of the palate may be considered as a clinical differential diagnosis in which local pain, swelling, epistaxis, nasal discharge, epiphora, diplopia, and numbness are some of the features.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…In mucormycosis, patients, an early sign of the disease is facial cellulitis, paresthesia, nasal discharge, necrotic turbinate, fever, headache, and lethargy. [ 7 ] However, many of these symptoms were absent in this patient, in contrast to other findings. Squamous cell carcinoma of the maxillary sinus or malignant salivary gland tumor arising from the accessory glands of the palate may be considered as a clinical differential diagnosis in which local pain, swelling, epistaxis, nasal discharge, epiphora, diplopia, and numbness are some of the features.…”
Section: Discussioncontrasting
confidence: 79%
“…[ 3 6 ] Our patient was COVID-positive previously and was on corticosteroids for the same which is a well-known predisposing factor for mucormycosis. [ 3 7 ] This fungal infection generally originates from the paranasal sinuses. In our patient, initially, the most probable route of infection was of the maxillary sinus following the fungal spore inhalation that led to the development of mucormycosis causing damage to the nerve plexus innervating the teeth, which may be the original cause of the dental pain.…”
Section: Discussionmentioning
confidence: 99%
“…This correlation suggests that C. parapsilosis clones might have colonized the hospital surfaces, which increases the risk of recirculating among patients along the time and, in parallel, increases the risk of invasive infections among the most fragile ones. Previous studies, in fact, have shown, not only an increase incidence of C. parapsilosis infections in COVID-19 patients [34], but also other fungal diseases, such as Covid Associated Pulmonary Aspergillosis (CAPA) [35][36][37], mucormycosis [38][39][40] and Candida infections [41,42] (see reviews in [43,44]).…”
Section: Resultsmentioning
confidence: 99%
“…The clinical manifestations of the disease are variable. Pulmonary mucormycosis symptoms could be nonspecific, including dyspnea, cough, fever, hemoptysis, and chest pain [ 24 , 25 ]. Therefore, the diagnosis of mucormycosis requires multilayered management that includes clinical symptoms, radiographic patterns, and fungal culture analysis [26] .…”
Section: Discussionmentioning
confidence: 99%